Serum C - Reactive Protein Level as a Predictor of New-Onset Postoperative Atrial Fibrillation in Off-Pump Coronary Artery Bypass Grafting - Muhammad Saqib,; Asghar, Muhammad Imran; Khan, Khalid Naveed; Abbasi, Waleed Ahmed; Javed, Yasir; Abbasi, Attiya Najeeb (Indus Journal of Bioscience Research, 2025)
Background: Postoperative atrial fibrillation (POAF) complicates up to 30% of coronary artery bypass grafting procedures and is linked to prolonged hospitalization, increased stroke risk, and higher mortality. Although off‑pump CABG (OPCAB) avoids cardiopulmonary bypass–induced inflammation, POAF remains common, suggesting that even minimal surgical trauma provokes an inflammatory environment sufficient to trigger arrhythmia. Serum C‑reactive protein (CRP) is an inexpensive, readily available marker of systemic inflammation; if elevated early after surgery, it may identify patients at higher arrhythmic risk and thus guide targeted prophylaxis. Methods: In this analytical cross‑sectional study, 100 consecutive OPCAB patients (age 35–70 years) were enrolled at the Armed Forces Institute of Cardiology/NIHD, Rawalpindi. Daily serum CRP was measured from postoperative day (POD) 0 through POD5. Patients were stratified into two groups CRP